2022
DOI: 10.3389/fphar.2022.1023878
|View full text |Cite
|
Sign up to set email alerts
|

WTAP mediates the anti-inflammatory effect of Astragalus mongholicus polysaccharide on THP-1 macrophages

Abstract: Background:Astragalus mongholicus polysaccharides (APS) have anti-inflammatory, antioxidant and immunomodulatory effects. Recent studies have demonstrated the epigenetic regulation of N6-methyladenosine (m6A) in the development of inflammation. However, the effect of APS on m6A modification is unclear. Here, for the first time, we investigate the mechanism of m6A modification in APS regulation of THP-1 macrophage inflammation.Methods: We treated LPS-induced THP-1 macrophages with APS at different concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…WTAP mediated the m6A modification of NLRP3 mRNA, and WTAP mRNA levels were positively correlated with pro‐inflammatory cytokines and NLRP3 inflammasome 25 . Long et al 26 confirmed that astragalus mongholicus polysaccharides exerted anti‐inflammatory effect by reducing WTAP‐mediated m6A modification in THP‐1 macrophages. To sum up, differential m6A methylation of WTAP may play a pro‐inflammatory role by upregulating its mRNA expression in our study.…”
Section: Discussionmentioning
confidence: 95%
“…WTAP mediated the m6A modification of NLRP3 mRNA, and WTAP mRNA levels were positively correlated with pro‐inflammatory cytokines and NLRP3 inflammasome 25 . Long et al 26 confirmed that astragalus mongholicus polysaccharides exerted anti‐inflammatory effect by reducing WTAP‐mediated m6A modification in THP‐1 macrophages. To sum up, differential m6A methylation of WTAP may play a pro‐inflammatory role by upregulating its mRNA expression in our study.…”
Section: Discussionmentioning
confidence: 95%
“…Research has shown that m6A may have clinical benefits in the management of AS. WTAP regulates m6A modification expression in THP-1 macrophages [42] to exert anti-inflammatory effect of APS. WTAP mediated the injurious effects of myocardial I/R by augmenting cell apoptosis and ER stress through a mechanisms involving the modulation of m6A modification on ATF4 mRNA [43] .…”
Section: Discussionmentioning
confidence: 99%
“…It has several bio-activities, including anti-inflammatory, proliferative, and immune-regulating effects, and a molecular weight of 3.6 × 10 4 Da ( Sun et al, 2021a ). Studies have demonstrated that APS significantly abrogates LPS-induced IL-6 levels in THP-1 macrophages ( Long et al, 2022 ). ABCA1 expression in foam cells exposed to TNF-α increases in response to APS ( Wang et al, 2010a ).…”
Section: Antiatherosclerotic Herbal Medicine Potentially Targeting Tr...mentioning
confidence: 99%